Development of PeCiKu TAHeS Educational Media (Hand Washing Habits and Short Nails for Grat and Healthy Children) to Increase Knowledge and Attitudes to Prevent Covid 19 at Tanjungsari 2 Elementary School, Blitar City - Mohamad Miftachul Ulum; Sri Mugianti; Imam Sunarno (Universitas Islam Balitar, 2021)
Promotion of healthy lifestyle habits of washing hands and short nails in pre-childrenat Tanjungsasi 2 Elementary School is one form of prevention against deviant attitudes andlifestyles. This study used the Pre-Experimental method: The One Group Pretest-PosttestDesign. The research subjects consisted of 60 elementary school students in grades 3 and 4divided into groups of 5 students each as users of the APE Educational Media PeCiKuTAHeS and 30 parents/guardians/teachers, 1 psychologist as an assessor of EducationalMedia Educational Game Tools PeCiKu TAHeS at Tanjungsari 2 Elementary School BlitarCity. The research object was the effectiveness of PeCiKu TAHeS Educational Game Tool(APE) in increasing the hand washing habits and short nails. Collecting data by givingquestionnaires before and after being given treatment to measure the hand washing habitsand short nails. and a media assessment checklist for media eligibility. The results of thepaired sample t-test showed that p = 0.000 (because p < ) then Ho was rejected and Ha wasaccepted, so there was a significant difference in the hand washing habits and short nailsbefore and after being given an intervention in the form of simulation games with PeCiKuTAHeS Educational Game Tool (APE), so it could be concluded that PeCiKu TAHeSEducational Game Tool (APE) was feasible and effective in increasing the habit ofwashing hands and short nails in schoolchild.